Metabolic syndrome cannot mask the changes of faecal microbiota compositions caused by primary hepatocellular carcinoma. (5th April 2021) - Ni, J.; Fu, C.; Huang, R.; Li, Z.; Li, S.; Cao, P.; Zhong, K.; Ge, M.; Gao, Y.
Abstract: Both hepatocellular carcinoma (HCC) and metabolic syndrome are closely associated with the composition of the gut microbiota (GM). Although it has been proposed that elements of the GM can be used as biomarkers for the early diagnosis of HCC, whether metabolic syndrome results in a misrepresentation of the results of the early diagnosis of HCC using GM remains unclear. We compared the differences in the faecal microbiota of 10 patients with primary HCC, six patients with type 2 diabetes mellitus (T2DM), seven patients with arterial hypertension, six patients with both HCC and T2DM, and 10 patients with both HCC and arterial hypertension, as well as 10 healthy subjects, using high‐throughput sequencing of 16S rRNA gene amplicons. Our results revealed a significant difference in the GM between subjects with and without HCC. The 49 bacterial genera out of the 494 detected genera were significantly different between the groups. These results show that changes in the GM can be used to distinguish between subjects with and without HCC, and can resist interference of T2DM and arterial hypertension with the GM. The results of the present study provide an important basis for the clinical auxiliary diagnosis of HCC by detecting the GM. Abstract : Significance and Impact of the Study: Both hepatocellular carcinoma (HCC) and metabolism syndrome are closely associated with gut microbiota composition. However, whether metabolic syndromes will misrepresent the results of early diagnosis of HCC through gut microbiota is still unclear. In the study, we found a significant difference in the gut microbiota between the subjects with HCC and without HCC. Forty‐nine bacterial genera were detected and might be used as an auxiliary tool for clinical diagnosis of HCC. These results implied that changes of gut microbiota could be used to distinguish HCC and non‐HCC subjects, and could resist interference of metabolism syndrome to gut microbiota.